Индонезийские СМИ о специальной военной операции России (Indonesian media about Russia's special military operation) - Syurkani, Panca; Muzykant, Valerii L. (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The Russian-Ukrainian military conflict often makes headlines in many media outlets around the world, including media in Indonesia. However, unfortunately, some media outlets publish fake news regarding the Russian-Ukrainian military conflict. This study examines fake news about Russia's special military operation in Indonesian media. The research method used is descriptive-qualitative. The data collection methodology was carried out by observing various Indonesian media outlets that published fake news related to the Russian-Ukrainian military conflict in Indonesian media. The collected data was then carefully analysed. Based on the analysis, it was established that several media outlets in Indonesia have been proven to disseminate false information regarding the Russian-Ukrainian military conflict that took place in 2022. While some of the above reports related to the Russian-Ukrainian army conflict have been proven fake news or hoaxes, the government does not impose sanctions on journalists or media outlets that publish such information. This is because journalists and media did not check the legitimacy of the information and did not fact-check. After verifying that the government has taken some steps to restore order in this area, the amount of fake news regarding the current Russian-Ukrainian military conflict has decreased significantly.